Impacto de la oferta y consumo de productos y/o servicios tecnológicos en las familias del cantón Quito, para el período 2006 - 2011 - Jaramillo García, Gabriela Inés (2013)
This research project was developed in order to know the reality of information technology and communication in the city of Quito, focused on families and focuses on four types of technologies such as the use of television, the computer, the Internet and mobile phone, which have generated significant changes in families over the past five years (2006-2011), this in order to know and has increased its demand and supply, and further define the impact they have had on society. Through each of the chapters made, it was determined the problem and the relevant aspects of the study. Initially described the objectives, rationale, problem, hypothesis and methodology under which developed the project, points that served as foundation for the order to reach conclusions and make recommendations.